Distribution moments of 2D-graphs as descriptors of DNA sequences - Bielinska-Waz, Dorota Joanna; Nowak, Wieslaw; Waz, Piotr; Clark, Timothy; et al. (Chemical Physics Letters, 2007)
We propose the statistical moments of mass-density distributions (created for two orthogonal directions) as new descriptors of DNA sequences. The distributions are derived using a 2D-dynamic representation technique proposed in our previous paper in which the sequence is coded by a set of point masses properly distributed in 2D-space. (c) 2007 Elsevier B.V. All rights reserved.